Pengaruh formulasi pupuk cair berbasis limbah organik dan penambahan konsorsium mikroba pelarut fosfat terhadap pertumbuhan tanaman cabai rawit (Capsicum frutescens L.) - Yuliatiningsih, Ni Putu; Darmayasa, Ida Bagus Gede; Defiani, Made Ria (Jurnal Biologi Udayana, 2022)
Chili pepper plant is one of the horticultural plants that have high nutritional value and economic value. Increasing chili production can be done by improving soil fertility through optimal and environmentally friendly fertilization. Rice dishwater can be used as a liquid organic fertilizer (LOF) combined with molasses and phosphate solubilizing microbes (PSM). The research objective was to explore the use of LOF formulations on the growth of chili pepper plants and determine the appropriate ratio between rice dishwater and molasses with the addition of a consortium of PSM in formulating LOF. The study was conducted using a one-factor completely randomized design with four replications. There are seven treatment, namely Y1 =  first control (without treatment); Y2 =  second control (commercial LOF); Y3 = 5% rice dishwater + 5% molasses + 10 mL consortium of PSM; Y4 = 10% rice dishwater + 10% molasses + 10 mL consortium of PSM; Y5 = 15% rice dishwater + 15% molasses + 10 mL consortium of PSM; Y6 = 20% rice dishwater + 20% molasses + 10 mL consortium of PSM; and Y7 = 25% rice dishwater + 25% molasses + 10 mL consortium of PSM. The Y7 treatment gave a good response to the growth of chili pepper plants.